Gestão de incêndios florestais: existem evidências empíricas do conhecimento tácito acumulado? - Duarte Alexandre da Costa Pereira (2021)
Years of dealing with forest fires lead to tacit knowledge emerging and accumulating among institutions responsible for fire fighting and the population's safety. Although this information is characterized by being informal and implicit, which means it has not been properly identified, registered, disseminated nor analyzed, it might often be a decisive factor on these operations' success, which stresses the importance of solving the problems inherent to tacit knowledge's nature, such as avoiding the loss of information every time the person that holds it changes post. With this in mind, applying methods such as expert elicitation, the distribution of a questionnaire among members of various institutions, and comparing the tacit knowledge identified against the empirical evidence available, 41 tacit knowledge units were cataloged and analyzed, resulting on an ordered list for the priority with which each of these units should be submitted to a process of scientific evaluation. The questionnaire showed that the percentage of agents that already knew of the existence of each unit of tacit knowledge presented was on average 65%, and so was the average percentage of participants that accepted the information of each unit as true. The most notorious differences in dissemination and acceptance happened between people from different levels of action, and the information that the night is the most favorable time of the day to fight fire is highlighted as being consistently the most disseminated and accepted piece of information, with percentages above 90% in all conducted analysis, and was therefore deemed to be the unit of knowledge with the highest scientific evaluation priority. This study is a crucial step towards the conversion of the tacit knowledge present in this organizations into explicit knowledge because, after the identification of said tacit knowledge, it was able to substantiate the decision of which units of knowledge should be scientifically evaluated first, contributing this way to the improvement of the forest fire integrated management system in Portugal.